Female elite sports achievements in Iran. The Case of the First Olympic Medalist - Ziaee, A.; Van Sterkenburg, J.; Van Hilvoorde, I. (International Review for the Sociology of Sport, 2023)
The present study aims to identify the societal implications of the first-ever Iranian female medalist in the Olympics to date. We explored the meanings given to Kimia Alizadeh's success within Iranian society. We collected data through an examination of online news agencies and social networking sites using Leximancer software, a computer-assisted program for qualitative content analysis. This analysis uncovered four main themes: `women's sports and the dynamics of local-global policy`, `hope and determination`, `pride in light of hijab`, and `meaningful and historic medal`. It was concluded that the societal implications of this medal-winning are more important than the quality of the medal itself within Iranian society. We also suggest assessing Iranian sportswomen within their own socio-cultural context.